Compressive strength of concrete containing rubber particles from recycled car tires confined with textile reinforced mortar (TRM) jackets - Papakonstantinou, Christos; Skyrianou, Ioanna; Koutas, Lampros (Technical Annals, 2024)
This study examines the mechanical characteristics of concrete incorporating recycled rubber aggregates as a partial substitute for natural aggregates. The concrete is confined with fibre textile jackets using an inorganic matrix (TRM). The experimental program includes studying the mechanical properties of concrete containing recycled aggregates compared to conventional concrete, through uniaxial compression tests of cylindrical specimens of 100 mm diameter and 200 mm height. Furthermore, the mechanical properties of confined concrete specimens with one or two layers of basalt fibre mesh in a cementitious matrix are examined. The findings underscore a reduction in the compressive strength of concrete when substituting natural aggregates with rubber, accompanied by an augmented deformation capacity. The incorporation of an inorganic matrix proves effective in enhancing compressive strength, particularly with the addition of more confinement layers. These results collectively suggest the feasibility of employing this environmentally friendly "green" concrete with TRM in applications prioritizing high deformability.